Stotan! - Crutcher, Chris (New York : Greenwillow, 1986)
A high school coach invites members of his swimming team to a memorable week of rigorous training that tests their moral fiber as well as their physical stamina.
"Ages 12 up"--Jacket.
Notable/Best Books (A.L.A.).
School Library Journal starred.
Wilson's Junior High School.
6.3
Young Adult
Keywords: High schools -- Fiction; Schools -- Fiction; Swimming -- Training -- Fiction; High schools -- Fiction; School stories; Swimming -- Training -- Fiction